Bank Syariah: Antara Konsepsi dan Implementasi - Ririn Noviyanti (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2018)
The development of Islamic banks up to now should be appreciated, there will still be some challenges that must be faced in order to make this institution even better. This study aims to discuss in depth related to the background of the formation of Islamic banks, opportunities and challenges faced. The conclusion of this study is that some of the challenges faced are as follows: problems of human resources (HRD), capital problems, regulatory problems, service network problems, product innovation problems, socialization problems. The strategies needed to anticipate some obstacles to the development of Islamic banks. First, improving the quality of human resources in the field of Islamic banking. Second, there are more progressive efforts from practitioners, government and ulama to encourage the fulfillment of the legality of shari'ah instruments so that syari'ah bank space is broader. Third, improving the quality of Islamic banks with the support of academics, so that the construction of Islamic finance institutions is more rational and acceptable to all groups. Fourth, a more aggressive socialization of Islamic banks.